Lost in translation? Ghost music in recent Japanese Kaidan films and their Hollywood remakes. Issue 2 (1st November 2010) - Wierzbicki, James
Western audiences in recent years have been intrigued by the cinematic phenomenon popularly known as J-Horror. Critical attention has been paid to more to the Hollywood remakes than to the original Japanese films. Comparing such Hollywood films as The Ring, The Grudge, and Dark Water with their models, this essay focuses on the various soundtracks' use of a particular ghostly noise. It argues that whereas the soundtracks of the Japanese Kaidan films in various ways sustain an aesthetic/theatrical tradition that is centuries old, the Hollywood remakes miss an important point by appropriating the sound but not its context.